Experimental study of physical and rheological properties of grape juice using different temperatures and concentrations. Part II: Merlot. (March 2018) - de Castilhos, Maurício Bonatto Machado; Betiol, Lilian Fachin Leonardo; de Carvalho, Gisandro Reis; Telis-Romero, Javier
Abstract: The effect of the temperature and concentration on rheological behavior of Merlot juice concentrates was assessed using a rheometer over a wide range of temperature (1–66 °C) and concentrations (13.6–45.0 Brix) at shear rates of 0.84–212.1 1/s. The Ostwald-De Waele was the best rheological model fitted the data (R 2  = 0.99967 and relative error = 7.99%). The consistency levels were significantly reduced with the increase of temperature and increased with the increase of the concentrations, ranging from 0.1766 (13.6 Brix at 66 °C) to 19.1140 Pa·s n (45.0 Brix at 1 °C). The flow behavior index presented no up or downward pattern when the temperatures were compared. The flow activation energy ranged from 13.95 (45.0 Brix) to 24.88 KJ/mol (21.0 Brix) with a R 2  = 0.9822 and 0.9812, respectively. Density and specific heat were influenced by both temperature and concentration; however, thermal conductivity was only influenced by concentration and temperature in two cases (13.6 and 29.0 Brix). The data showed the potential use of Merlot juice concentrates as wine chaptalization agent in winemaking. Graphical abstract: Highlights: Rheological behavior of Merlot juices was analyzed. The grape concentrates followed Ostwald-De Waele law and pseudoplastic behavior. Density and specific heat were influenced by both temperature and concentration. Thermal conductivity was influenced by the different concentrations assessed. Thermal conductivity was influenced by temperature in 13.6 and 29.0 Brix.